An Exploring Students' Perceptions Of Peer Feedback On English Speaking - Ulfatun Hasanah; Bradhiansyah Tri Suryanto (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study investigates students' perceptions of peer feedback in English speaking classes at the Foreign Language Development Institute (LPBA), Nurul Jadid University. Using a qualitative descriptive method, data were collected through classroom observations and in-depth interviews with eight intermediate-level learners. The results reveal that students generally hold positive views toward peer feedback, recognizing its role in increasing their awareness of language errors, improving fluency and pronunciation, and fostering greater speaking confidence. Despite these benefits, challenges such as vague suggestions and ineffective feedback delivery were noted. The study highlights the importance of training students in how to give and receive feedback effectively, suggesting that with proper guidance, peer feedback can be a valuable tool in developing speaking proficiency